Effects of daily functional acorn cake consumption on insulin resistance in individuals with obesity or overweight and the metabolic syndrome: a placebo-controlled randomised clinical trial. Issue 7 (14th April 2023) - Mohammadi-Sartang, Mohsen; Babajafari, Siavash; Kohansal, Atefeh; Rostami, Hosein; Pourmahmoudi, Azizollah; Sohrabi, Zahra
Abstract: The metabolic syndrome is a multi-factorial condition and functional foods need more investigation as novel adjunct treatments for this group. This study aimed to determine the effects of daily consumption of a functional acorn cake in conjunction with energy restriction (119.50 kJ) on individuals with overweight or obesity and the metabolic syndrome. In this randomised double-blinded study, eighty-four participants were randomly allocated to either an energy-restricted diet plus two servings (2 × 30 g)/d of functional acorn cake (a cake made of acorn for the intervention group) (FC) ( n 42) or an energy-restricted diet plus placebo cake (PC) ( n 42). Body composition and biochemical parameters were measured before and after 10 weeks of intervention. Seventy-three participants completed this trial. No differences in loss of body weight, waist circumference, fat mass, fasting blood glucose and blood pressure were shown between two groups. Body weight decreased by 4·2 (sd 1·9) kg and 5·1 (sd 2·8) kg in PC and FC groups, respectively. Compared with PC, the consumption of FC resulted in a significant reduction in serum insulin ( P = 0·02), homoeostasis model assessment for insulin resistance ( P = 0·02), high-sensitivity C-reactive protein ( P = 0·04) and a significant increase in adiponectin concentration ( P = 0·04). Although lipid metabolism did not differ among groups, total cholesterol and HDL-cholesterol improved non-significantly in the FC group. Functional acorn cake as an adjunct to energy restriction could possibly improve insulin resistance in individuals with obesity. Further research is needed to elucidate whether functional acorn cake can be used as a preventive strategy for the metabolic syndrome in individuals with obesity.